THE IMPLEMENTATION OF AUDIO LINGUAL METHOD IN TEACHINGLISTENING TO THE SECOND YEAR STUDENTS OF SMK 2MUHAMMADIYAH ANDONG BOYOLALI - RAHMAWATI, SHINTA (2010)
This research aims at describing the implementation of Audio Lingual Method in teaching listening to the second year students of SMK 2 Muhammadiyah Andong Boyolali, describing the problems faced by teacher and students in implementing the method, and describing the student response to the implementation of Audio Lingual Method in teaching listening. The research was done in SMK 2 Muhammadiyah Andong Boyolali. The writer took the second year students of SMK 2 Muhammadiyah Andong Boyolali as the subject of the study. To collect the data the writer conducted observation, interview, and analyzed document. Observation is an activity in certain situation to get the data. Interview is a dialogue done by the writer to get information from the teacher. It was conducted by asking the teacher about the implementation of the method in English teaching learning process. In analyzing the data, the writer uses descriptive qualitative because this research is non-statistic analysis and the process of analyzing is done together with the process of collecting the data. Based on the result of data analysis the writer finds that the teacher implements Audio Lingual Method in teaching listening. It can be observed from the student's activity in the classroom. The students are active enough but the teacher dominates the class activities. The material used by teacher is nonauthentic materials. The problems faced by teacher are about selection of the material and the time management. The problems faced by students are limited vocabulary, the speed and accent of native speaker said, the difficulty in interpreting the message and difficulty to concentrate to the lesson. The students' response to the implementation of Audio Lingual Method in teaching listening can be divided into two groups; they are slow learners and good learners. Key word : Audio Lingual Method, teaching listening.